Novel zinc(II) complexes [Zn(atc-Et)2] and [Zn(atc-Ph)2]: In vitro and in vivo antiproliferative studies - De Lopes, Erica O. [UNESP]; De Oliveira, Carolina G.; Da Silva, Patricia B. [UNESP]; Eismann, Carlos E. [UNESP]; Suárez, Carlos A. [UNESP]; Menegário, Amauri A. [UNESP]; Leite, Clarice Q. F. [UNESP]; Deflon, Victor M.; Pavan, Fernando R. [UNESP] (MDPI, 2016)
Cisplatin and its derivatives are the main metallodrugs used in cancer therapy. However, low selectivity, toxicity and drug resistance are associated with their use. The zinc(II) (ZnII) thiosemicarbazone complexes [Zn(atc-Et)2] (1) and [Zn(atc-Ph)2] (2) (atc-R: monovalent anion of 2-acetylpyridine N4-R-thiosemicarbazone) were synthesized and fully characterized in the solid state and in solution via elemental analysis, Fourier transform infrared (FTIR), ultraviolet-visible (UV-Vis) and proton nuclear magnetic resonance (1H NMR) spectroscopy, conductometry and single-crystal X-ray diffraction. The cytotoxicity of these complexes was evaluated in the HepG2, HeLa, MDA-MB-231, K-562, DU 145 and MRC-5 cancer cell lines. The strongest antiproliferative results were observed in MDA-MB-231 and HepG2 cells, in which these complexes displayed significant selective toxicity (3.1 and 3.6, respectively) compared with their effects on normal MRC-5 cells. In vivo studies were performed using an alternative model (Artemia salina L.) to assure the safety of these complexes, and the results were confirmed using a conventional model (BALB/c mice). Finally, tests of oral bioavailability showed maximum plasma concentrations of 3029.50 _g/L and 1191.95 _g/L for complexes 1 and 2, respectively. According to all obtained results, both compounds could be considered as prospective antiproliferative agents that warrant further research.
Keywords: Acute toxicity; Antiproliferative activity; Artemia salina L; Cancer; Oral bioavailability; Zinc(II) complexes